Parenting in the digital age: Attitudes, controls and limitations regarding children's use of ICT - Gur, Duygu; Turel, Yalin Kilic (Pergamon-Elsevier Science Ltd, 2022)
Today, with the development of technology, many possibilities are offered to users; however, these possibilities bring along some risks and threats. It is very important to ensure that users, especially teenagers, can benefit from the possibilities of technology at the highest level by minimizing the existing risks. At this point, the roles, attitudes and behaviors of parents have an important effect. The purpose of this study is to reveal the attitudes, behaviors, controls and limitations of middle school students' parents towards their children's use of information technologies. For this purpose, data were collected from parents through survey and interviews. The participants of the study consisted of 354 parents of 6th and 7th grade students from seven public schools and four private schools. The parents filled out a questionnaire. Also, semi-structured interviews were conducted with 13 volunteer parents. According to the results, parents 'attitudes towards their children's ICT use were positive and they especially supported their use of ICT for educational purposes. However, it was revealed that parents were concerned about the possible risks and security threats that their children may encounter in virtual environments, and therefore they take precaution in order to prevent their children from possible risks by informing, controlling and limiting their children. Based on the results, while children benefit from digital opportunities, they need to prevent themselves from digital risks as well through precautions and interventions with the support of school-parent cooperation.
Keywords: Digital parenting; Information and communication technologies (ICT); Parental control; Limitations; Online risks